The effectiveness of simulation-based training in general health practitioner education - Alshammari, Yousef Fehaid Hawas; Alharbi, Mudi Naif; Alanazi, ‏Huda Fawaz; Aldhahawi , Bandar Khulaif; Alshammari, Fahad Mohammed; Alsuwaydaa, Rawaf Hussain; Alenezi, Saad Ghanem; Alshammari, Bandar Awad; Alshammari, Rikan Mashan; Alshammari, Brahim Madhour; Jabal, Afnan Mohammed Bin; Alruwaili, Enas Salem Rasheed; et al. (International journal of health sciences, 2021)
The objective of this research was to examine the efficacy of simulation-based training in the field of nursing education. A thorough search of electronic databases was done to identify relevant research using a systematic literature review. The researchers used inclusion criteria to identify studies that specifically examined the effects of simulation-based training in nursing education on a range of outcomes. The review included both quantitative and qualitative investigations. Thematic analysis was conducted on the retrieved data in order to uncover prevalent patterns and topics pertaining to the efficacy of simulation-based training. The assessment of the listed studies' quality was conducted using suitable methodologies. The review's results underscored the advantages of incorporating simulation-based training into nursing school, including enhanced information acquisition, competence enhancement, and increase in self-assurance. Nevertheless, obstacles such as financial implications, personnel training, and student apprehension were also recognized. The research underscores the need for more investigation and agreement among nursing experts in order to develop a robust body of data about the efficacy of simulation-based training. The results of this research enhance comprehension of the influence of simulation-based training in the field of nursing education and provide suggestions for its integration and enhancement.